Influence of CYP3A5 and SLCO1B1 polymorphisms on atazanavir/r concentrations in Thai HIV-infected patients - Noppaket Singkham (2019)
© 2019 Future Medicine Ltd. Aim: To evaluate the influence of genetic polymorphisms on plasma trough concentrations of atazanavir (ATV) and ritonavir (RTV). Patients & methods: The concentration-to-dose ratios were compared between different genotype groups of CYP3A5, ABCB1, SLCO1B1 and NR1I2 in 490 patients. Multiple regression analysis was used to examine the association between genetic and clinical factors and log-transformed concentration-to-dose ratio of ATV and RTV. Results: Higher concentrations of ATV and RTV were significantly associated with CYP3A5 6986 GG and SLCO1B1 521 TC or CC. Female patients had significantly higher ATV plasma concentration than male patients. Conclusion: Genetic polymorphisms and gender are factors affecting the variability of ATV and RTV concentrations in the Thai population. Thus, genetic testing is worth considering when atazanavir + low dose ritonavir is prescribed.